2015
DOI: 10.4143/crt.2014.085
|View full text |Cite
|
Sign up to set email alerts
|

Population-based Incidence and Survival for Primary Central Nervous System Lymphoma in Korea, 1999-2009

Abstract: PurposePrimary central nervous system lymphoma (PCNSL) is an uncommon brain tumor accounting for 2%-5% of all primary brain tumors. Few population-based analyses of survival for patients with PCNSL have been conducted, particularly in Asian countries.Materials and MethodsUsing the Korea National Cancer Incidence Database, 1,062 cases of PCNSL newly diagnosed from 1999 to 2009 were analyzed. The crude rate, age-standardized rate (ASR), and annual percent change were calculated. To estimate the observed survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 13 publications
5
29
0
Order By: Relevance
“…This pattern somewhat mirrored, yet lagged behind, that observed in the United States; according to United States population data spanning an overlapping calendar period, there was a similar rapid increase in rate during the 1980s, followed by a relative plateau [ 30 ]. The incidence of PCNSL is higher in men than women in Australia, consistent with observations from other population-based cohorts [ 2 , 10 , 12 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This pattern somewhat mirrored, yet lagged behind, that observed in the United States; according to United States population data spanning an overlapping calendar period, there was a similar rapid increase in rate during the 1980s, followed by a relative plateau [ 30 ]. The incidence of PCNSL is higher in men than women in Australia, consistent with observations from other population-based cohorts [ 2 , 10 , 12 ].…”
Section: Discussionsupporting
confidence: 89%
“…Present incidence of PCNSL in the Australian population is greater than that reported for Korea (i.e., 0.25 per 100,000 person-years) [ 10 ], but consistent with figures reported in Japanese, Spanish, French, Irish, Swedish, Dutch, and North American population studies, which range between 0.4 and 0.5 per 100,000 person-years [ 2 , 11 , 12 , 13 , 27 , 28 , 29 ]. While reports from Western Europe and Asia indicate ongoing annual increases [ 9 , 10 , 11 , 12 , 13 , 27 ], incidence of PCNSL has plateaued in the United States [ 30 ]. The overall increase in incidence of PCNSL in Australia that we have observed, was characterized by a rapid ‘jump’ in the rate in the 1990s, which was most apparent for persons aged 70–79 years, after which the rate plateaued.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, previous studies found that older age and pretreatment PS are significant prognostic factors. [ 2 3 5 6 10 11 13 14 ] Most previous studies defined older age as >60 years,[ 3 6 13 16 17 18 ] whereas others used >50 years as the cut off. [ 2 5 11 14 ] In our study, older age was a significant predictor of poor outcomes in the univariable analysis, and age was a poor prognostic factor, but not significant, in the multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] The disease incidence is more common in immunocompromised patients. [ 2 3 ] However, this rate has increased in healthy elderly within the current decade. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%